Faktor Perilaku Perpindahan Merek (Brand Switching) : Studi Pada Pegawai Pengguna Telepon Seluler Merek Samsung Di Kantor Bupati Minahasa Tondano - Kapojos, Januard .R. (Universitas Sam Ratulangi, 2017)
The purpose of this research is to search and find what factor that will be consumer consideration should it occur on doing brand switching and decided to use cellular phone Samsung. Population in this research are civil service and administrative staff which totaled 163 people at the Regional Regent Office Minahasa Tondano. The total sample 100 respondents. Data Processing using SPSS v22. Technique Analyze using Factor Analyze Technique. The Result point out that variable Satisfied Consumer, Variety Seeking, Product Quality and Price are factor to be reconsidered on brand switching from the other cellular phones to Cellular Phone Samsung. In this Factor analysis results factor formed The Price according to Product Quality, Product Quality, Satisfaction in searching Variation, Promotion Word Of Mouth.Keywords: Satisfied Consumer, Variety Seeking, Product Quality, PriceÂ